Antenatal depressive symptoms and adverse perinatal outcomes - Despina Pampaka; Stefania I. Papatheodorou; Mohammad AlSeaidan; Rihab Al Wotayan; Rosalind J. Wright; Julie E. Buring; Douglas W. Dockery; Costas A. Christophi (BMC, 2021)
Abstract Background The association of antenatal depression with adverse pregnancy, birth, and postnatal outcomes has been an item of scientific interest over the last decades. However, the evidence that exists is controversial or limited. We previously found that one in five women in Kuwait experience antenatal depressive symptoms. Therefore, the aim of this study was to examine whether antenatal depressive symptoms are associated with preterm birth (PTB), small for gestational age (SGA), or large for gestational age (LGA) babies in this population. Methods This was a secondary analysis based on data collected in the Transgenerational Assessment of Children's Environmental Risk (TRACER) Study that was conducted in Kuwait. Logistic regression analysis was used to examine whether antenatal depressive symptoms assessed using the Edinburgh Depression Scale (EDS) were associated with preterm birth, small for gestational age, and large for gestational age babies. Results A total of 1694 women had complete information about the outcomes of interest. Women with depressive symptoms in pregnancy had increased, albeit non-significant, odds of having PTB (OR = 1.41; 95%CI: 0.81, 2.45), SGA babies (OR = 1.26; 0.80, 1.98), or LGA babies (OR = 1.27; 0.90, 1.79). Antenatal depressive symptoms had similar increased odds for the three outcomes even after adjusting for several covariates though none of these reached statistical significance. Conclusions In the present study, the depressive symptoms in pregnancy did not predict adverse birth outcomes, such as PTB, SGA, and LGA, which adds to the currently non-conclusive literature. However, further research is needed to examine these associations, as the available evidence is quite limited.